A Choledochal Cyst Resulting in Obstructive Jaundice in a Case with Gallbladder Agenesis: Report of a Case and Review of the Literature - Boyuk, Abdullah; Kirkil, Cuneyt; Karabulut, Koray; Sozen, Selim; Demirelli, Salih (Galenos Publ House, 2012)
Co-existence of gallbladder agenesis and choledochal cyst is a very rare congenital anomaly of the extrahepatic biliary system. The literature presents only five cases with this combination. Herein, we report the sixth case. Gallbladder agenesis is usually asymptomatic, while choledochal cyst often presents symptoms before adolescence. This is the report of a 42-year-old female patient with gallbladder agenesis and choledochal cyst leading to obstructive jaundice. Radiological diagnosis of choledochal cysts is not difficult. However, in cases with gallbladder agenesis, cystic dilatation in the choledochus may be misdiagnosed as mislocation of the gallbladder or contracted and/or sclero-atrophic gallbladder.
Keywords: Gallbladder agenesis; choledochal cyst; obstructive jaundice